2002
DOI: 10.1038/sj.bjc.6600203
|View full text |Cite
|
Sign up to set email alerts
|

Transhiatal vs extended transthoracic resection in oesophageal carcinoma: patients' utilities and treatment preferences

Abstract: To assess patients' utilities for health state outcomes after transhiatal or transthoracic oesophagectomy for oesophageal cancer and to investigate the patients' treatment preferences for either procedure. The study group consisted of 48 patients who had undergone either transhiatal or transthoracic oesophagectomy. In an interview they were presented with eight possible health states following oesophagectomy. Visual Analogue Scale and standard gamble techniques were used to measure utilities. Treatment prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Mortality rates vary between 1 and 8% and major morbidity occurs in almost 50% of the patients undergoing resection [32, 33]. The impact of surgery on QoL has been investigated in several prospective studies using validated reliable questionnaires [22, 34, 35].…”
Section: The Impact Of Surgery For Oesophageal Cancer On Qolmentioning
confidence: 99%
“…Mortality rates vary between 1 and 8% and major morbidity occurs in almost 50% of the patients undergoing resection [32, 33]. The impact of surgery on QoL has been investigated in several prospective studies using validated reliable questionnaires [22, 34, 35].…”
Section: The Impact Of Surgery For Oesophageal Cancer On Qolmentioning
confidence: 99%
“…On the other hand, transthoracic esophagectomy led to significantly higher early pulmonary morbidity, higher costs, and a longer stay in the ICU. When analyzing patients' treatment preferences, De Boer et al (4) concluded that most patients preferred the transthoracic procedure over the transhiatal procedure. Apparently, the patients were prepared to undergo a more demanding procedure to optimize their chances for definite cure from this malignant disease (4).…”
Section: Discussionmentioning
confidence: 98%
“…Postoperative morbidity and mortality rates are substantial, and almost all patients stay in the ICU postoperatively. Due to the magnitude of the operation, physical, emotional, and social effects are large, with potentially serious consequences for short-term and longterm QoL (3,4). Because of these serious consequences and because of the limited survival after an esophagectomy, information about the expected postoperative QoL could be an important factor in future approaches toward different patients with esophageal cancer (5).…”
mentioning
confidence: 98%
“…It is compositional, and the weights are drawn up directly. Our review identified 42 studies using direct choice questions in one form or another, ranging from questionnaires consisting only of direct choice questions [40] to studies using direct choice as an additional method-for example, with a VAS [41].…”
Section: Other Methodsmentioning
confidence: 99%